Select aspects relating to defenses to strict product liability as introduced by the Consumer Protection Act of 68 of 2008 - Van Heerden, C.M. (Corlia) (University of Pretoria, 2016)
Mini Dissertation (LLM)--University of Pretoria, 2016.